Novelty of 18F–fluorocholine computed tomography (18-FCHPETCT) in predicting quality of life in malignant breast cancer patients - Zakaria, Mohd Hazeman; Ahmad Saad, Fathinul Fikri; Shaharuddin, Shazreen; Kamaluddin, Nor Rizan; Esa, Ezalia; Mat Yusoff, Yuslina (International Agency Energy Agency (IAEA), 2024)
This is a retrospective study. 21 patients with known case primary/recurrent breast carcinoma (BIRADS 4/5 breast lesions) underwent [ 18F]FCH PET/CT prior to biopsy. Histopathological examination (HPE) is obtained and dichotomized into malignant and benign groups and HER2-ve and HER2+ve groups. Maximum standardized uptake value (SUVmax (g/dl) was used to predict two groups of variables for cellular breast cancer aggressiveness. QOL assessed SF-36®, SF36v2®, SF- 1,2® and SF-12v2® Health Surveys. Questionnaires used under Medical Outcome Trust and QOL domains: Global Health Status (GHS), Physical Function (PF), Role Function (RF) and Social Function (SF).